A new species from southwestern China of Clematoscenea (Psocoptera: Psocidae), with a key to known species - Liu, Luxi; Li, Fasheng; Liu, Zhiqi (Zootaxa, 2013)
Clematoscenea spinosus sp. n. is described and illustrated as the second species of this genus from China, and an English redescription of C. yunnanica Li is provided. Updated keys are given to the known species, together with distributional data.